Nanodiamond plates as macroscale solid lubricant: A "non-layered" two-dimension material. (15th October 2022) - Liu, Yanfei; Yu, Shengtao; Wang, Wenzhong
Abstract: Two-dimensional (2D) materials with a layered structure can realize extremely low coefficient of friction (COF) at the nanoscale or microscale. However, the highly ordered sliding interface is difficult to be obtained with conventional layered 2D materials, leading to a significantly higher COF at the macroscale. Hence, a novel strategy using "non-layered" 2D materials for macroscale lubrication is proposed in this study. As a "non-layered" 2D material, nanodiamond (ND) plates with thickness as low as several nanometers were used to fabricate solid lubrication coatings with thickness of approximately 3 μm using drop casting method. The ND plates coating reduced the COF by 54.55% compared to that of the ND particles coating, and by 55.13 and 41.92% compared to graphene and MoS2 coatings, respectively. A transfer layer was formed on the ball surface and a tribofilm with ND plates highly aligned with the sliding direction was formed in the wear track, where the sliding between the ND plates or ND plates and the friction pairs dominates the lubrication performance. Most importantly, the wrinkles and wrapped edge sites commonly observed on layered 2D materials can be eliminated by the high mechanical performance of ND plates, leading to an ordered sliding interface, thus lowering the macroscale COF. This study provides implications for the development of macroscale lubrication systems with "non-layered" 2D materials for engineering applications. Graphical abstract: Image 1 Highlights: Nanodiamond plates exhibit excellent solid lubrication performance at the macroscale. Tribofilms with nanodiamond plates can be formed during the friction process. An ordered sliding interface can be achieved due to the high mechanical performance of nanodiamond plates. "Non-layered" two-dimensional materials are promising candidates for macroscale lubrication systems.